Senescent alveolar type II epithelial cells-secreted GDF15 promotes silicosis progression via interfering intercellular communication - Wenxiu Lian; Demin Cheng; Wenqing Sun; Ting Wang; Xinying Jia; Zhenhua Jia; Yi Liu; Chunhui Ni (Ecotoxicology and Environmental Safety)
Background: Silicosis is a chronic fibrotic pulmonary disease caused by consistent inhalation of respirable crystalline-free silica dust. The senescence of alveolar epithelial type II cells (ATII) is considered the initiation of pulmonary fibrosis. As a secreted protein, growth differentiation factor 15 (GDF15) was found intimately associated with the severity of lung diseases via senescence. Therefore, we speculate that GDF15 may involved in silica-induced pulmonary fibrosis. Methods: Co-culture was performed to observe the pro-fibrotic effect of GDF15, which is secreted from the silica-induced senescence ATII cells, on peripheral effector cells. We further explored GDF15-related signaling pathways via ChIP and IP assays. GDF15 siRNA lipid nanoparticles, anti-aging compound β-nicotinamide mononucleotide (NMN), and the Chinese traditional drug Bazibushen (BZBS) were used individually to intervene silicosis progress. Results: SiO2 and etoposide-stimulated MLE-12 cells showed senescence phenotype and secreted substantial GDF15, which is consistent with over-expressed GDF15 in lung tissues from silica-induced pulmonary fibrosis. The results further demonstrated that senescence ATII cells could facilitate co-cultured epithelial cell epithelial-mesenchymal transition (EMT) and fibroblast activation in a GDF15-dependent manner. Mechanistically, p53 regulates GDF15 transcription and secretion in senescence ATII cells. Moreover, secreted GFD15 performed its pro-fibrotic role by directly binding to TGF-βR via autocrine and paracrine manners. Also, lipid nanoparticles targeting GDF15 or cell senescence inhibitor NMN and BZBS showed efficient anti-fibrotic effects in vivo. Conclusions: Our results elucidate that senescence ATII cell-secreted GDF15 plays a vital role in promoting silicosis by influencing surrounding cells, and provides scientific clues for the selection of potential therapeutic drugs for silicosis.